The prevalence of occupational asthma and rhinitis among woodworkers in south-eastern Nigeria - Aguwa, E N; Okeke, T A; Asuza, M C (Tanzania Journal of Health Research, 2007)
Wood dusts are known to cause respiratory disorders like rhinitis and asthma. This study was therefore done todetermine the magnitude of the problem among woodworkers in south-eastern Nigeria exposed to high level of wood dust.Five hundred and ninety one woodworkers were selected using a stratified random sampling. The prevalence of woodworkrelatedrhinitis and asthma were then observed in the study population. Also the peak expiratory flow rate (PEFR) of eachwoodworker was obtained. The prevalence of occupational rhinitis was 78%, while that of asthma was 6.5%. As period ofwoodwork increased the prevalence of rhinitis and asthma increased (rhinitis: χ2 trend = 53.015, df = 1, P = 0.000). Forasthma, χ2 trend =19.721, df = 1, P = 0.000). Also the PEFR significantly became low with increasing years of exposure towoodwork (χ2 trend = 75.965, df = 1, P= 0.000). In conclusion the prevalence of rhinitis and asthma in woodworkers washigh and significantly increased with years of working as a woodworker. Keywords:woodwork, peak expiratory flow rate, rhinitis, asthma, wood dust, Nigeria Tanzania Health Research Bulletin Vol. 9 (1) 2007: pp.52-55